Filtering Antenna With High Selectivity Using Multiple Coupling Paths From Source/Load to Resonators - Zhang, Bohai; Xue, Quan (IEEE transactions on antennas and propagation, 2018)
This communication presents a filtering antenna with high selectivity using multiple coupling path from source/load to resonators. The high selectivity of the filtering antenna's boresight gain response is achieved by a novel coupling scheme, which induces additional coupling between source/load and nonadjacent resonators to construct cross coupling paths. Thanks to the extra cross-coupling paths, the filtering antenna can generate a maximum of N radiation nulls with N resonators. Besides, a resonator using a combination of open-ended stub and short-ended stub is adopted to construct this novel coupling scheme more easily. For demonstration, a three-order filtering stacked patch antenna with a center frequency of 2.3 GHz and a fractional bandwidth of 15.2% is fabricated. Two independently controllable radiation nulls are located at 1.97 and 2.61 GHz. Unidirectional radiation patterns have been achieved with cross polarization lower than -20 dB and back lobes lower than -18 dB.